Low-intensity pulsed ultrasound irradiation ameliorates gut inflammation and neuroinflammation in mice with DSS-induced colitis - Shan Tian; Yugang Hu; Yanxiang Zhou; Jiao Li; Jian Liu; Qing Zhou (APL Bioengineering)
Ulcerative colitis (UC) is a lifelong autoimmune disease associated with a high prevalence of mental disorders. An abnormal gut–brain axis plays a key role in UC. Low-intensity pulsed ultrasound (LIPUS) has been reported to alleviate neuroinflammation. This study aimed to evaluate the therapeutic effects of LIPUS in an experimental colitis model. A mouse model of colitis induced by dextran sulfate sodium (DSS) was established to evaluate the therapeutic effects of LIPUS irradiation. Intestinal inflammation and the mucosal barrier were detected using reverse transcriptase polymerase chain reaction and immunofluorescence staining. The key proteins of the NLRP3 inflammatory pathway in different groups were measured by western blotting. 16S rRNA sequencing and ultra-performance liquid-chromatography tandem mass spectrometry were applied for the detection of bacteria, metabolites, and neurotransmitters. LIPUS irradiation significantly improved the mucosal barrier in DSS-induced colitis mice and relieved intestinal inflammation and neuroinflammation by downregulating the NLRP3 inflammatory pathway. 16S rRNA sequencing showed that LIPUS irradiation significantly upregulated the abundance of Bacteroides and glutamate metabolism. Metabolic analysis revealed that the most significant metabolites between the DSS + LIPUS and DSS groups were mostly involved in alanine, aspartate, and glutamate metabolism. The detection of neurotransmitters revealed that the levels of gamma-amino butyric acid (GABA) were significantly upregulated in DSS-induced colitis mice after LIPUS irradiation, and correlation analysis revealed a positive correlation between GABA and Bacteroides. LIPUS irradiation not only alleviated gut inflammation and neuroinflammation by regulating the NLRP3 inflammatory pathway in DSS-induced colitis mice but also increased GABA levels by upregulating Bacteroides, indicating that LIPUS might be a promising therapeutic technology for UC treatment.